Load frequency control in power systems - Guo, Xiangyu (2014)
The constant changing of loading of a power system is one of the criteria that affect the power system stability. This changing load will affects the system frequency and must be compensated with the power generated from the generator. A power system may have a serious instability problem when the frequency change of the power system differs from the nominal frequency by 5 percent. As more large scale multi area power plant system is built to support the electricity need, the power plant control systems become more complicated. Thus it is necessary to design a load frequency controller that can handle the parametric uncertainties and nonlinearity of a real power system. In this project the multi area power plant system and its dynamics are studied. Furthermore the modeling of the three-area power plant using SIMULINK and simulation of the system using a decentralized robust controller when subjected to system parameter uncertainties and the unpredictable change of load are discussed. Simulation results show that the decentralized load frequency controller can ensure that the system is stable for all bounded parametric uncertainties, even in the presence of generation rate constraint.